The photocopier: re-evaluating the substance of a heterogeneous technology - Jones, Evan (2019)
Marshal McLuhan once wrote that ‘societies have always been shaped more by the nature of the media by which men communicate than by the content of the communication’ . He argued that the methods and technologies we use to communicate shape our culture and ultimately our human behaviour. The intention of this thesis is the examination of a piece of technology that has been largely overlooked within the field of art history and visual culture, but the creation of which has influenced a significant cross-section of contemporary western culture; namely the photocopier. Our dominant perception of the photocopier is of a banal technology, with little or no creative potential, and whose sphere of influence is marked most strongly by its association with the office and the workplace. Although its use in the workplace is well established, and its role in creating one of America’s most successful companies, the Xerox Corporation, is well documented, its history and influence is far from clear-cut. The creation of the photocopier initiated an entirely new market for office copying machines, doing away with nearly all its predecessors. It has been responsible for the creation of a subsection of folklore called Xeroxlore or photocopy lore, which is study of a form of individual subversion which takes place within the workplace environment. The photocopier played a significant role in the British punk scene of the 1970s and the 1990s American Riot Grrrl movement. It has also been used by artists from the early 1960s, right through to the high point of its use as an artistic tool in the 1980s and 1990s. It continues to play a role in current sub- and counter-cultural movements and is still being used by countless creators of fanzines, comics, and other material.